Socialization of the Benefits of Fermenting Cattle Milk into Yogurt as a Probiotic Food Product for Housewife Community of Sruni Village, Musuk, Boyolali - Sri Sinto Dewi; Stalis Norma Ethica; Wikanastri Hersoelistyorini (Universitas Mathla'ul Anwar Banten, 2019)
Boyolali Regency is among districts in Indonesia, which still has poverty issues and receives direct cash assistance from the government. Yet, villages of the regency including Sruni at Musuk sub-district has been known as one of the main producers of fresh cow milk for the Central Java region.There has been no attempt to process fresh milk into food products of higher economic value at Sruni Village. Meanwhile, results of the strengths, weaknesses, opportunities, and threats (SWOT) analysis at Musuk showed that the region has the potential to be developed for dairy industry. Therefore, through socialization program, community empowerment should be initiated by socializing benefits of fermenting cattle milk into yogurt as a probiotic food product. The socialization had been carried out for 12 housewives in the village of Sruni through two small-class seminars in April 2019. Evaluation was conducted by comparing the number of correct answers from participants’ answers recorded on questionnaire given prior and after each of both seminars. Percentage of improved answers were presented in histograms and then analyzed. As results, the first seminar produced in average 47.4% improved answers, while the second seminar could generate in average 27.3% improved answers. The results showed that in general, the conducted socialization program was quite successful in improving understanding of Sruni villagers on the benefits of fermenting cattle milk into yogurt as a probiotic food product.